The Kristen Muhammadiyah and the Dynamics of Interfaith Harmony: A Hermeneutic Study of Pluralism in Indonesia - Faizah, Nurul; Isa Anshori; Harun Al-Rasyid (Journal of Islamic Philosophy and Contemporary Thought, 2024)
Religious harmony in Indonesia has become an important issue amid ongoing social dynamics. Based on Jorge Gracia’s hermeneutic approach, this study examines the phenomenon of Kristen Muhammadiyah (Krismuha)—harmonious interactions between Christian and Muhammadiyah communities in Muhammadiyah educational environments in non-Muslim-majority areas. The method used is descriptive-qualitative with text analysis techniques applied to the work Kristen Muhammadiyah by Abdul Mu’ti and Fajar Riza Ul Haq. The study results indicate that interactions between Muhammadiyah and the Christian community in the field of education occur without theological coercion but are based on sociological relationships that uphold openness, comfort, and respect for each other’s identities. These findings affirm that the inclusive pluralism model promoted by Muhammadiyah is capable of building interfaith trust through education. Gracia’s hermeneutic approach demonstrates a balance between the interpretation of normative Islamic texts and the pluralistic social context faced by Muhammadiyah. The Krismuha phenomenon contributes to interfaith diplomacy at the grassroots level, strengthening social cohesion and enriching Indonesia’s living laboratory of pluralism. This study recommends the development of similar models to expand the scope of interfaith harmony in Indonesia.